Magnetic resonance of paramagnetically doped materials - Wilman, James (2017)
Colloidal quantum dots (QDs) allow for the tuning of dopant concentration as well as flexibility in the engineering of the surrounding medium. This thesis explores the use of magnetic resonance techniques and the development of hardware in order to characterize paramagnetically doped materials, in particular Mn-doped PbS colloidal QDs, and assess their potential for applications in quantum technologies such as quantum information processing (QIP).